2022
DOI: 10.3389/fpsyg.2022.929270
|View full text |Cite
|
Sign up to set email alerts
|

Understanding preservice teachers' affective responses to VR-enabled scientific experiments

Abstract: Preservice teachers' preparedness, perception, and affect toward certain technology systems influence the student acquisition of science knowledge, process skills, teaching innovation, and willingness to use technology in their classroom. The purpose of this study was to explore teachers' affective responses to a virtual reality-enabled scientific experiment (VaSE) system. Fifty-one preservice teachers majoring in educational technology participated in the study. They were divided into two groups, and their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Of them, most studies examined teachers' self‐efficacy after experiencing XR technologies ( n = 7) (e.g., Bautista & Boone, 2015; Gundel et al, 2019; Nissim & Weissblueth, 2017; Pendergast et al, 2022). Several studies also examined the effect of class size on teachers' physiological and psychological stress reactions (Huang et al, 2023b), motivational affordance (Jong, 2023), affective state (Xie et al, 2022), emotional and mood states (Stavroulia et al, 2019), and the effect of the shot size on the psychical distance between virtual characters and their viewers (Kim et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, most studies examined teachers' self‐efficacy after experiencing XR technologies ( n = 7) (e.g., Bautista & Boone, 2015; Gundel et al, 2019; Nissim & Weissblueth, 2017; Pendergast et al, 2022). Several studies also examined the effect of class size on teachers' physiological and psychological stress reactions (Huang et al, 2023b), motivational affordance (Jong, 2023), affective state (Xie et al, 2022), emotional and mood states (Stavroulia et al, 2019), and the effect of the shot size on the psychical distance between virtual characters and their viewers (Kim et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding XR technologies, 33 studies reported applying VR technologies in teacher education, followed by MR ( n = 14) and AR ( n = 5). About 58% studies reported to construct XR learning environments based on various platforms, including TLE TeachLivE™ (Bautista & Boone, 2015; Dawson & Lignugaris Kraft, 2017; Dieker et al, 2019; Fraser et al, 2020; Judge et al, 2013; Pas et al, 2016), Mursion (Gundel et al, 2019; Gundel & Piro, 2021; Piro & O'Callaghan, 2019; Rosati‐Peterson et al, 2021), Unity 3D (Arican & Özçakir, 2021; Huo et al, 2021; Stavroulia et al, 2016, 2019; Stavroulia & Lanitis, 2020; Xie et al, 2022), Breaking Bad Behaviours (Chen, 2022; Lugrin et al, 2018; Seufert et al, 2022), SketchUp 3D (Stavroulia et al, 2016; Sveinbjörnsdóttir et al, 2019), iSee (Pendergast et al, 2022), Didascalia Virtual‐Classroom (Manero et al, 2022), Google Expeditions app (Artun et al, 2020), SIMLab™ (Rappa, 2019), Second Life (Cheong, 2010), Superscape (Katz, 1999), StoryBoard Artist 7 (Kim et al, 2017), Heart AR (Celik et al, 2020), Diva Distro (Nissim & Weissblueth, 2017), and TaleBlazer (Aivelo & Uitto, 2016).…”
Section: Resultsmentioning
confidence: 99%